Diabetes and treatment of chronic heart failure in a large real‐world heart failure population. (4th December 2021) - Radhoe, Sumant P.; Veenis, Jesse F.; Linssen, Gerard C.M.; van der Lee, Chris; Eurlings, Luc W.M.; Kragten, Hans; Al‐Windy, Nadea Y.Y.; van der Spank, Aukje; Koudstaal, Stefan; Brunner‐La Rocca, Hans‐Peter; Brugts, Jasper J.
Abstract: Aims: Although diabetes mellitus (DM) is a common co‐morbidity in chronic heart failure (HF) patients, European data on concurrent HF and DM treatment are lacking. Therefore, we have studied the HF treatment of patients with and without DM. Additionally, with the recent breakthrough of sodium–glucose cotransporter 2 (SGLT2) inhibitors in the field of HF, we studied the potential impact of this new drug in a large cohort of HF patients. Methods and results: A total of 7488 patients with chronic HF with a left ventricular ejection fraction <50% from 34 Dutch outpatient HF clinics between 2013 and 2016 were analysed on diabetic status and background HF therapy. Average age of the total population was 72.8 years (±11.7 years), and 64% of the patients were male. Diabetes was present in 29% of the patients ( N = 2174). Diabetics had a worse renal function (mean estimated glomerular filtration rate 56 vs. 61 mL/min/1.73 m 2, P < 0.001). Renin–angiotensin system inhibitors were less often prescribed in diabetics compared with non‐diabetics (79% vs. 82%, P = 0.001), while no significant differences regarding other guideline‐recommended HF drugs were found. Target doses of beta‐blockers (23% vs. 16%, P < 0.001), renin–angiotensin system inhibitors (47% vs. 43%, P = 0.009), and mineralocorticoid receptor antagonists (57% vs. 51%, P = 0.005) were more often prescribed in diabetics than non‐diabetics. Based on the latest trials on SGLT2 inhibitors, 31–64% of all HF patients would fulfil the eligibility or enrichment criteria (with vs. without N‐terminal prohormone BNP criterion). Conclusions: In this large real‐world HF registry, a high prevalence of DM was observed and diabetics more often received guideline‐recommended target doses. Based on current evidence, the majority of patients would fulfil the enrichment criteria of SGLT2 trials in HF and the impact of this new drug class will be large.